Grow globally opportunities for your middle-market company around the world - Pearl, Mona, 1964-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Discover proven strategies and solutions for successful participation in the global marketWith less than fifty percent of middle market US companies succeeding at going global, corporate executives need to know how to build effective global execution platforms that will allow their organizations to thrive in a global economy. Filled with case studies and indispensable checklists, Grow Globally guides executives in crafting an actionable global strategy that will not only stand the test of change--but that will also be on target, on budget, and on time. Reveals how to anticipate change in global decision-making and execution Explores how to identify trends and respond to differences between internal corporate culture and the target culture Includes case studies, checklists, process visuals and resources, plus a website that hosts online tools and materials As the world becomes more dependent on technology and trade borders gradually disappear, your company needs to acquire the tools and skills necessary to compete in the global market. Grow Globally presents the skills needed to build a global execution platform that will keep your organization relevant and competitive in the international landscape"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Small business -- Management; International business enterprises -- Management; Globalization -- Economic aspects; Electronic books